Südosteuropa : Journal of Politics and Society (De Gruyter Oldenbourg, 2016)
Südosteuropa is an English-language, multidisciplinary journal for the exploration of critical societal issues and processes related to southeastern Europe after the systemic changes of 1989/90. It serves as a forum for current work in Southeast and East European Studies, including Political Science, Sociology, International Relations, Contemporary History, Economics, Anthropology, Law Studies, Gender Studies as well as Cultural Studies.